Pelatihan Pembuatan Video Animasi dan Kuis Interaktif untuk Meningkatkan Kompetensi Guru Adaptif di Desa Tonasa - Mawarni, Sella; Yanti, Nur Eva; Ibrahim, Nur Wahyuningsih; Hartoto; Irwan (LOSARI DIGITAL, 2024)
Partners in this community service activity are the Kelompok Kerja Guru (KKG) of Tonasa Village and Thematic KKN students of the Educational Technology Study Program, State University of Makassar. The implementation of the Kurikulum Merdeka needs to be supported by improving the adaptive skills of teachers in facilitating the learning process, especially in terms of utilizing appropriate technology in learning. Important skills needed include skills in developing learning media and implementing learning assessments. This interactive quiz and animated video training activity aims to improve the adaptive competence of teachers in Tonasa Village. More specifically, this training is expected to be able to: (1) produce an animated video using the Canva application; (2) produce an interactive quiz using the Wordwall application; and (3) integrate animated videos and interactive quizzes into the learning process in the classroom. The methods used in this activity are presentations, practices, and discussions. The training is carried out through three stages, namely the planning, implementation, and evaluation and reflection stages. The majority of teachers in Tonasa Village already have and often use the Canva application because they have an education account, but so far they have only used the application to make presentations. This training provides new insights while facilitating teachers to learn to use Canva as an application to create creative animated videos. The training on creating interactive quizzes using the Wordwall application was very well received by teachers in Tonasa Village, because the application offers more than 18 attractive templates for students. The results of students' work on the Wordwall application can be used by teachers as a form of formative assessment that supports the learning process. Training on creating interactive quizzes and animated videos can provide insight and skills so that teachers are able to answer the challenges of the times and students' needs for innovative, creative, and fun learning.